2007
DOI: 10.1038/ismej.2007.70
|View full text |Cite
|
Sign up to set email alerts
|

Phytoplankton carbon fixation gene (RuBisCO) transcripts and air-sea CO2 flux in the Mississippi River plume

Abstract: River plumes deliver large quantities of nutrients to oligotrophic oceans, often resulting in significant CO 2 drawdown. To determine the relationship between expression of the major gene in carbon fixation (large subunit of ribulose-1,5-bisphosphate carboxylase/oxygenase, RuBisCO) and CO 2 dynamics, we evaluated rbcL mRNA abundance using novel quantitative PCR assays, phytoplankton cell analyses, photophysiological parameters, and pCO 2 in and around the Mississippi River plume (MRP) in the Gulf of Mexico. Lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
1
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 39 publications
1
26
1
2
Order By: Relevance
“…A number of CCM variants, differing in manner of operation and efficiency, are found among different phytoplankton, and nutrient availability is also known to play a significant role in modulating CCMs (reviewed by Giordano et al, 2005). From our results alone it is therefore difficult to judge whether increase in atmospheric CO 2 might have a greater effect when production is based on regenerated nutrients, or whether our observations possibly reflect that small and intermediate sized osmotrophs are not equipped with carbon concentration mechanisms as efficient as the diatoms and therefore benefit more from increased CO 2 levels (John et al, 2007). An observed a shift from diatoms to nanophytoplankton when Hare et al, 2007 incubated phytoplankton communities at elevated pCO 2 support the latter explanation.…”
Section: Discussioncontrasting
confidence: 48%
“…A number of CCM variants, differing in manner of operation and efficiency, are found among different phytoplankton, and nutrient availability is also known to play a significant role in modulating CCMs (reviewed by Giordano et al, 2005). From our results alone it is therefore difficult to judge whether increase in atmospheric CO 2 might have a greater effect when production is based on regenerated nutrients, or whether our observations possibly reflect that small and intermediate sized osmotrophs are not equipped with carbon concentration mechanisms as efficient as the diatoms and therefore benefit more from increased CO 2 levels (John et al, 2007). An observed a shift from diatoms to nanophytoplankton when Hare et al, 2007 incubated phytoplankton communities at elevated pCO 2 support the latter explanation.…”
Section: Discussioncontrasting
confidence: 48%
“…Although overall primary productivity is highest in plume samples, whole and 0.2 mm size-fractionated primary productivity demonstrated that a higher proportion of the total primary productivity in the plume was driven by larger phytoplankton, such as diatoms, rather than Synechococcus (John et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The large subunit of form I RubisCO is encoded by the cbbL genes, which further divide form I RubisCO into four forms (IA, IB, IC, and ID) (Tabita et al 2008). cbbL genes encoding forms IA, IB, IC, and ID have been widely used as phylogenetic biomarkers to characterize biodiversity of autotrophic microorganisms in diverse habitats, e.g., oceans, lakes, and soils (John et al 2007;Kong et al 2012a, b;Yuan et al 2012a).…”
Section: Introductionmentioning
confidence: 99%